The Hypocrisy of Justice in the Belle Epoque - Martin, Benjamin F. (Book collections on Project MUSE., 1999)
The Dreyfus Affair of the 1890s and the violent controversies that surrounded it appeared to pass two very different judgments on the France of the Third Republic. The outcome o the trial-Captain Dreyfus convicted without guilt and the real traitor acquitted despite guilt-demonstrated without question the extraordinary hypocrisy of the military justice system. But the furor raised by Dreyfus' conviction and the agitation for his release suggested that the injustice of the courts' verdict was uncharacteristic of French society; that for France as a nation the rendering of justice was paramount.